Sagot :
1. [tex]x = - 2, \: x = 2
[/tex]
Solving Steps
[tex] {2x}^{2} - 8 = 0[/tex]
[tex] {x}^{2} - 4 = 0[/tex]
[tex] {x}^{2} = 4[/tex]
[tex]x = + 2[/tex]
[tex]x = - 2 \\ x = 2[/tex]
2. [tex]x = - 3 \\ x = 3[/tex]
Factor the expression
[tex] {x}^{2} - 9 = 0[/tex]
Separate into possible cases
[tex](x - 3) \times (x + 3) = 0[/tex]
Solve the equation
[tex]x - 3 = 0 \\ x + 3 = 0[/tex]
The equation has 2 solutions
[tex]x = 3 \\ x = - 3[/tex]
3. [tex]x = - 3 \\ x = 3[/tex]
[tex]3 {x}^{2} = 27[/tex]
Divide both sides
[tex] {x}^{2} = 9[/tex]
Move the constant to the left
[tex] {x}^{2} - 9 = 0[/tex]
Factor the expression
[tex](x - 3) \times (x + 3) = 0[/tex]
Separate into possible cases
[tex]x = 3 \\ x = - 3[/tex]
The equation has 2 solutions